Awareness of cervical cancer among women aged 18-25 years in rural areas - Patil, Kajal M.; Sawant, Siddhanth S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Cervical cancer is the 2nd most common cancer in India. It is the most common cause of death in developing countries. According to the current global status of 2016, the age-standardized incidence rate of cervical cancer varies between 5.6 to 24.3 per 1 lakh women in India. Human papillomavirus (HPV) is responsible for subclinical/clinical lesions in cervical cancer. Cervical cancer occurs early and strikes at the productive period of a woman’s life. The vaccines against HPV are bivalent (Cervarix), the quadrivalent vaccine (Gardasil) was licensed in the country in 2008 and a non-valent vaccine was licensed in 2018. Methods: An observational study was conducted on 149 women in rural areas from Patan taluka (Satara district). A questionnaire was made after referring to similar studies. Informed consent was taken. A validated questionnaire with 9 questions was given to the person and was asked to fill them. Results: Awareness about cervical cancer was 15.4%. Awareness about risk factors especially genital warts, and sexual activity before 18 was 30.4% and 8.69% respectively. The least commonly known symptoms were vaginal discharge (26.0%), heavy vaginal bleeding (21.7%). Awareness about cervical screening methods was 8.69%. 18.75% knew about vaccination against cervical cancer. Conclusions: This study shows poor knowledge about cervical cancer and its symptoms, risk factors and prevention methods in the population surveyed. Thus, extensive health education for the public along with the inclusion of the HPV vaccine in the National Immunization Programme is required.